Research of professional burnout of teachers - E. Smirnova; Т. Poshtareva (Вестник Северо-Кавказского федерального университета, 2022)
The problem of professional deformation of teachers is exacerbated along with the negative realities that modern society has faced in the form of a pandemic that has swept the world, an increase in the pace of life, and, at the same time, growing demands on the pedagogical community. The respondents were representatives of the teaching staff of three universities in the Stavropol Territory. The study showed that despite the different teaching experience and age of the respondents, they are all subject to professional deformation. In genera, the level of professional burnout of the studied teachers is above average. These results indicate the need to develop self-help programs, psychological support for teachers and correction of professional burnout. Thus, timely diagnostics, which allows for effective prevention and correction of the professional burnout syndrome, not only contributes to an increase in the level of psychological well-being of teachers, but also labor productivity. The more detailed the understanding of the level of development of each of the components of professional burnout, the more effective will be the measures to prevent and overcome it.